A highly reliable, impervious and sustainable triboelectric nanogenerator as a zero-power consuming active pressure sensor. Issue 2 (9th January 2020) - Vivekananthan, Venkateswaran; Chandrasekhar, Arunkumar; Alluri, Nagamalleswara Rao; Purusothaman, Yuvasree; Kim, Sang-Jae
Abstract : A water proof silicone elastomer based triboelectric nanogenerator for bio-mechanical energy scavenging and a zero-power consuming/self-powered pressure sensor. Abstract : The triboelectric effect is one of the most trending effects in energy harvesting technologies, which use one of the most common effects in daily life. Herein, an impervious silicone elastomer-based triboelectric nanogenerator (SE-TENG) is reported with a micro roughness-created silicone elastomer film and Ni foam as triboelectric layers with opposite surface charges. The surface roughness modification process was performed via a cost-effective soft lithography technique using sandpaper. The replicated film was then used as the negative triboelectric layer and porous Ni foam was used as the positive triboelectric layer. The device exhibited the advantage of high stability due to the porous nature of the Ni foam, which could not damage the roughness pattern of the elastomer film. The device generated a maximum electrical output of ∼370 V/6.1 μA with a maximum area power density of ∼17 mW m −2 at a load resistance of 1 GΩ. Furthermore, the SE-TENG device was packed using polyethylene to protect it from humidity and made to be a water-resistant SE-TENG (WR-SE-TENG). The device was stable under different percentages of relative humidity, showing a uniform electrical output in the range of 10% RH to 99% RH. This proves that the packing is highly resistant against moisture and humidity. The device was also used for demonstrating its capability in powering small electronic components such as charging commercial capacitors, glowing LEDs and powering wrist watches. Further, the WR-SE-TENG device was used to scavenge bio-mechanical energy from human motions and also used for a real-time application of zero power consuming/self-powered pressure sensors. As an active sensor, the device showed linear sensing behavior and a sensitivity of 0.492 μA kPa −1 .